Hubungan Jumlah Paritas Anak dengan Angka Kejadian Kanker Leher Rahim di Dr. Pirngadi Medan - Anisantaria Anisantaria; Meida Nugrahalia; Sartini sartini (Universitas Medan Area, 2017)
This reseach aims to determine the relationship between the number of parity of children with the incidence of cervical cancer in Dr. Pirngadi Medan 2012. The study was conducted in January 2013 in Dr. Pirngadi Medan. Materials in this study using medical colleagues data that is cervical cancer patients who come checked in RSUD Dr. Pirngadi Medan Year 2011-2012. The research method is done by analytical descriptive. The samples in this study were cervical cancer patients taken from medical record data at RSUD Dr. Pirngadi Medan Year 2011-2012. The results of the study were obtained by the largest KLR patients in the parity of more than 2 children (multiparas) (70.2%), then grandemultipara (26.9) and primipara (2.9%). Result of correlation of multipara relationship with cervical cancer stage obtained R value (18,23%), and grandemultipara with cervical cancer stage R value (0,92%). Regression results obtained by multiparous and grandemultipara positive and significant sign of cervical cancer incidence, which means multiparous and grandemultipara is not a determining factor of cervical cancer.